New materials of B2O3–Bi2O3–Me2O3 (Me = Yb, Lu) systems - Asadov, M. (D.Ghitu Institute of Electronic Engineering and Nanotechnologies, 2010)
It is shown that the Yb2O3–Bi2O3–B2O3 system gives a new Yb3Bi2B5O15 compound of a hexagonal crystallographic system. Based on the data on the nature of specimens and by means of X-ray study of obtained samples, we determined the boundaries of glass-formation regions in the Yb2O3–Bi2O3–B2O3 system. Homogeneous glasses were obtained in the following cuts: Bi2O3⋅B2O3 − Lu2O3–B2O3 up to 15 mol % Lu2O3; Lu2O3⋅B2O3−Bi2O3 up to 10 mol % Lu2O3; Bi2O3⋅B2O3 − Lu2O3⋅Bi2O3 up to 15 mol % Lu2O3. Eutectic coordinates of LnBO3– B2O3 (Ln = Се, Pr, Pm, Sm, Tb, Er) systems were calculated at first.